Moving from government to governance: addressing housing pressures during rapid industrial development in Kitimat, BC, Canada. Issue 10 (26th November 2021) - Ryser, Laura; Halseth, Greg; Markey, Sean
Abstract: In resource-based communities, housing can be a contributing asset or challenge to attracting and retaining workers and families. In Kitimat, BC, Canada, a housing crisis threatened vulnerable, low income, and middle income residents during a period of rapid growth associated with renewed industrial investments. Even though housing policy and public housing provision falls under provincial government jurisdiction, the crisis response was largely mobilized by local stakeholders. Drawing upon a five year tracking study, this paper traces the rise of new governance arrangements to address local housing pressures. These governance arrangements fostered greater community awareness of housing issues; strengthened relationships across community, industry, and some senior government stakeholders; and renewed local housing assets. This collective capacity to manage housing pressures, however, remains vulnerable due to public policy incoherence that undermines or fails to adequately support local governance initiatives.